2013
DOI: 10.1158/1940-6207.capr-12-0419
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-Carbinol and 3′,3′-Diindolylmethane Modulate Androgen's Effect on C-C Chemokine Ligand 2 and Monocyte Attraction to Prostate Cancer Cells

Abstract: Inflammation has a role in prostate tumorigenesis. Recruitment of inflammatory monocytes to the tumor site is mediated by C-C chemokine ligand 2 (CCL2) through binding to its receptor CCR2. We hypothesized that androgen could modulate CCL2 expression in hormone-responsive prostate cancer cells and thereby promote recruitment of monocytes. Given the inhibitory effect of broccoli-derived compounds indole-3-carbinol (I3C) and 3,3 0 -diindolylmethane (DIM) on androgen-dependent pathways, we also reasoned that I3C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
(41 reference statements)
0
8
0
1
Order By: Relevance
“…Among various inflammatory cytokines, IL-1b and IL-6 play important roles in the expression of differentiation factors and activation of osteoclasts, which results in CT degradation and bone resorption [26]. A previous study reported that DIM can reduce the expression of IL-1b and IL-6 to delay prostate tumour growth and angiogenesis [27]. In vitro, the effects of DIM on IL-1b and IL-6 Note: All results are expressed as means § SD.…”
Section: Putative Mechanism Of Action and Therapeutic Potentialmentioning
confidence: 99%
“…Among various inflammatory cytokines, IL-1b and IL-6 play important roles in the expression of differentiation factors and activation of osteoclasts, which results in CT degradation and bone resorption [26]. A previous study reported that DIM can reduce the expression of IL-1b and IL-6 to delay prostate tumour growth and angiogenesis [27]. In vitro, the effects of DIM on IL-1b and IL-6 Note: All results are expressed as means § SD.…”
Section: Putative Mechanism Of Action and Therapeutic Potentialmentioning
confidence: 99%
“…These indoles are known for their chemopreventive effects on hormone-dependent cancers such as prostate cancer [ 8 ]. It has been shown that I3C/DIM inhibit proliferation, migration, and invasion of prostate cancer cells in vitro by targeting a wide spectrum of signal pathways governing hormonal homeostasis, cell cycle progression, apoptosis, and DNA repair [ 9 , 10 , 11 ]. Several nuclear transcription factor-mediated pathways related to these biological processes have been reported to be modulated by I3C/DIM [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, both I3C and DIM appear to be pleotropic and can exert their effects through multiple pathways which include modulation of androgen-dependent pathways and the AHR mediated pathway [ 23 , 24 ]. Previously, we have shown that I3C and DIM, through androgen-dependent pathways, modulate the interaction between prostate cancer cells and macrophages by regulating the production of chemokine CCL2 by prostate cancer cells [ 29 ]. CCL2 is a pro-inflammatory chemokine that attracts monocytes to tumor sites [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…THP-1 is a monocytic cell line that can be differentiated into macrophage. Additionally, we have also shown that THP-1 can be attracted by cancer cells [ 29 ].…”
Section: Introductionmentioning
confidence: 99%